The Role of Auditing in Financial Risk Mitigation Amid Global Economic Disruption - Dailibas, Dailibas; Mutaufiq, Ali; Chaerudin, Chaerudin; Nasution, R.; Harahap, Muhammad Nasim (International Journal of Artificial Intelligence Research, 2024)
This research aims to explore the role of audit in managing financial risk amidst the complexity of global economic dynamics. By explaining in detail the contribution of audits in helping entities identify, manage and mitigate financial risks. This research uses qualitative research methods, focusing on the role of audit in managing financial risk amidst global economic dynamics. Through interviews with 20 respondents, including auditors and financial practitioners, analysis of financial reports, and literature studies, the research gained in-depth understanding. Interpretive methods are used to analyze the data, providing a theoretical and practical basis in explaining the contribution of audits to financial risk mitigation. The research results confirm that auditors do not only limit themselves to examining financial reports, but are actively involved in helping entities identify and manage financial risks. These findings provide a strong foundation for entities to face global economic uncertainty and ensure the reliability of financial information. Audits are identified as a key element in enterprise risk management. Auditors not only apply audit theory conceptually but also create practical guidelines for achieving successful operational risk management. In addition, the evolution of audit theory along with changes in the global economy shows the practical relevance of audit theory in responding to changing economic dynamics.